(untitled) (Basel Institute on Governance Working Papers, 2003)
Switzerland is frequently accused of being reluctant to take thorough measures to fight money laundering. Both the Swiss authorities and the banks in Switzerland strongly reject such accusations. We are convinced that our anti-money laundering measures are best market practice. What are the reasons for these markedly different viewpoints? Can they be explained by conceptual differences? Are the negative statements the result of insufficient knowledge of our legal provisions, or are they simply motivated by the political desire of the respective commentators to divert public attention from the deficient anti-money laundering policies in their own countries? A comparison of our measures with the most important competing financial centres could help to answer these questions. The SFS Stiftung Finanzplatz Schweiz – a foundation initiated by the foreign banks in Switzerland – commissioned Professor Mark Pieth of the Basel Institute on Governance to conduct a comparative study of anti-money laundering regulations in the UK, the US and Singapore, the three financial centres which closely compete with the Swiss private banking sector. Professor Pieth is a renowned expert in the field and has close contacts with the international experts who also contributed to the project with in-depth country studies.